Menjadi Orang Tua Hebat: Memahami Kesiapan Anak Memasuki Sekolah Dasar - Murni Hayati, Leni; Yulimarta, Esa; Sandi, Peki Fitra; Yanti, Sri (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2026)
School readiness is a crucial factor in determining children’s successful adaptation and learning processes at the elementary education level. However, many parents still interpret school readiness narrowly, focusing mainly on early academic skills. This community service program aimed to enhance parents’ and teachers’ understanding of children’s readiness to enter elementary school from a holistic perspective, including physical, cognitive, language, social-emotional, and independence aspects. The activity was conducted through an offline educational and participatory approach involving lectures and interactive discussions with parents and early childhood teachers in the IGTK of Sangir Balai Janggo District, Solok Selatan Regency. The results indicated an increased awareness among participants regarding comprehensive school readiness indicators and the strategic role of parents in supporting children during the educational transition period. This program contributes to strengthening family involvement as the primary environment in fostering children’s optimal school readiness.